1979
DOI: 10.1126/science.316188
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Induces Functional Antiprotease Deficiency in the Lower Respiratory Tract of Humans

Abstract: Current concepts of the pathogenesis of emphysema suggest that it results from an imbalance of elastase and antielastase activity within the alveolar structures. Although emphysema that is associated with hereditary deficiency of serum alpha 1-antitrypsin conforms to this scheme, the major risk factor in the more common form of emphysema is cigarette smoking. A study was designed to evaluate the premise that cigarette smoking may be associated with an acquired, functional defect in lung alpha 1-antitrypsin. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
2
2

Year Published

1984
1984
2012
2012

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 369 publications
(135 citation statements)
references
References 18 publications
4
127
2
2
Order By: Relevance
“…In the present study, the large increase in collagenase activity after treatment with CSE in combination with either IL-1␣ or IL-1␤ may result from induction of MMP activators. We know that cigarette smoke and interleukins increase protease production and reduce antiprotease activity in inflammatory lung cells (25)(26)(27)(28). The demonstration that SAECs produce proteases is significant because studies have shown that pathological changes in the small airways are linked to changes in airway resistance in emphysema (29, 30).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the large increase in collagenase activity after treatment with CSE in combination with either IL-1␣ or IL-1␤ may result from induction of MMP activators. We know that cigarette smoke and interleukins increase protease production and reduce antiprotease activity in inflammatory lung cells (25)(26)(27)(28). The demonstration that SAECs produce proteases is significant because studies have shown that pathological changes in the small airways are linked to changes in airway resistance in emphysema (29, 30).…”
Section: Discussionmentioning
confidence: 99%
“…The inactivation of ctrproteinase inhibitor might be produced by oxidation of a methionine residue near the proteinase inhibitory site, possibly by oxygen free radicals (23)(24)(25). It is known that oxygen free radicals generated by complement activated neutrophils or other processes are important mediators of tissue injury in a great variety of diseases (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo exposure to cigarette smoke has been shown to bring about a decrease in the elastase inhibitory capacity (EIC) in the serum of rats (55) as well as in pulmonary lavage fluids in humans (26,56), although these last reports have been the subject of recent controversy (57). The decreased EIC in these cases is not the result of a decreased level of alPI itself, but rather the result of the formation of an inactive form of the protein containing oxidized methionine residues (26).…”
Section: The Tar Radical(s) In Cigarette Smoke: Esr Studiesmentioning
confidence: 99%